Technopark in educational facilities - Bulgakova, Elena; Petrova, Larisa; Shulginova, Olga (project baikal, 2021)
The article covers the concept of technopark in higher educational institutions in the framework of the programs of adaptation of educational institutions to innovation forms of education. Knowledge about the subject is concretized on the basis of the study of the features of the technopark in the facility of the holding group MFUA - MITU-MACI. The authors describe the architectural solution for the technopark in the context of scientific activities on the elaboration of architectural solutions, advisory and rule-making activities.
Keywords: technopark; renovation of the original project; architectural assessment; field study; potential of areas; rule-making; regulation of conditions; layout